PHYSICAL EDUCATION, PROFESSIONALIZATION AND LABOR MARKET: AN ANALYSIS OF THE PROFESSIONAL PROJECT - Fonseca, Rubiane Giovani; Souza Neto, Samuel de [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2020)
We seek to understand how Physical Education has been organized in the labor market, with expansion of employment possibilities in recent years. We take Sociology of Professions as a theoretical lens and conduct a descriptive study based on data extracted from the microdata base of 2014 RAIS - Annual Social Information Report. As a result, we observed: a contingent of young professionals; larger presence of women in the various sectors of work; and low permanence in formal employment in the long term. We found high variability in salaries in different states, and between genders. We concluded that investment is needed in new analyzes about the macro-social context of the profession that consider that careers in Physical Education are conditioned to society's social, political, cultural and economic contingencies.
Keywords: Job market; Career mobility; Sociology; Professionalism